Aplikasi Interaksi Manusia Komputer Pada Pemodelan Sistem Informasi Perparkiran Gedung Bertingkat - Swamardika, I.B Alit; Adnyani, Ida Ayu Sri (Jurnal Ergonomi Indonesia (The Indonesian Journal of Ergonomic); Vol 5 No 1 (2019): Volume 5 No 1 Juni 2019DO - 10.24843/JEI.2019.v05.i01.p05, 2019)
The development of private vehicle ownership is very rapid, but it is not balanced by adequate supporting infrastructure such as roads and parking lots. Especially for parking lots, parking horizontally will be difficult to develop because of the limited land availability. The addition of parking lots can be done vertically by building a multi-storey parking building. So far, the existence of multi-storey parking buildings has not provided an information system on the availability of parking spaces. The form of multi-storey parking lots often makes the driver have to go around few times to find an empty space. This situations wasting of energy and time. This study aims to design an information system as application models in human-computer interaction, that will inform someone there is empty or already filled parking space, so that it can save time and make it easier for drivers to find parking spaces to park their cars. This information system prototype design consists of three main parts, called sensors, controllers, and displays. Car parking control system that works with an automatic portal (parking gate) along with a display screen for information on the location of empty parking spaces and those that have been filled. The portal will open if information states the parking lot is still available, and the portal will not open if information states the parking lot is full.